Ti/Cu/Kovar Multilayer Interlayer PTLP Diffusion Bonding Si3N4/Ht250 - Deku Zhang; Lian Zhang; Ning Zhou; Kehong Wang; Xiaopeng Li (Ceramics, 2022)
In this paper, partial transient liquid phase (PTLP) diffusion bonding between Si3N4 ceramics and Ht250 cast iron was carried out by using an Ti/Cu/Kovar/Cu/Ti interlayer. The effects of the heating temperature and holding time on the microstructure, formation mechanism, and mechanical properties of Si3N4/Ht250 cast iron joints were studied. The results show that the maximum shear strength of the joint is 112 MPa when the welding temperature is 1000 °C and the holding time is 1 h. In addition, the problems of Ti/Cu/Ti intermetallic compound formation and Cu/Si3N4 ceramic residual thermal stress in the joint can be effectively alleviated.